Associations between neutrophil-percentage-to-albumin ratio level and all-cause mortality and cardiovascular disease-cause mortality in diabetes population - Geng Shen; Yuting Liu; Can Zhou; Wei Luo; Yun-xiao Yang; Shuai Guo; Jiayi Yi; Lin Wang; Wei Li; Zhao-gong Zhi; Xiu-huan Chen; Chen Li; et al. (BMC Public Health)
Abstract Background The prevalence of type 2 diabetes mellitus (T2DM) remains high and biomarkers related to T2DM are needed to be investigated. This study aimed to investigate the association between neutrophil percentage-to-albumin ratio (NPAR) with all-cause mortality and the risk of cardiovascular disease (CVD) mortality in community-dwelling individuals with T2DM. Methods This prospective cohort study included 3602 adults aged 20 or above who were diagnosed with diabetes by the American Diabetes Association criteria in the US National Health and Nutrition Examination Survey (NHANES) database from 1999 to 2016, and followed up until 2019. Multivariable Cox proportional hazards regression models were utilized to determine the relationship between NPAR with all-cause mortality and cardiovascular disease (CVD) mortality. Restricted cubic spline regression analyses were employed to explore the nonlinear relationship between NPAR and cardiovascular disease (CVD) mortality. The assessment of nonlinearity was conducted using the likelihood ratio test. Results After adjustment, the risk ratio for all-cause mortality in the highest NPAR group (≥ 15.40) compared to the lowest serum NPAR reference group (< 13.30) was 1.62 (95% CI, 1.36, 1.94) with P values < 0.001. Nevertheless, the risk ratio for cardiovascular disease (CVD) mortality in the highest NPAR group (≥ 15.40) versus the lowest serum NPAR reference group (< 13.30) was 1.41 (95% CI, 0.99, 2.00) with a P value of 0.06. Among patients with T2DM, serum NPAR levels exhibited a nonlinear correlation with both CVD mortality risk and all-cause mortality risk, with P values < 0.001 for both. Conclusions This study identified a significant association between elevated levels of the neutrophil percentage-to-albumin ratio (NPAR) and an increased risk of all-cause mortality among individuals with type 2 diabetes mellitus (T2DM). Conversely, no correlation was found between NPAR levels and CVD mortality.